Biodiversity and Topographic Complexity: Modern and Geohistorical Perspectives. (March 2017) - Badgley, Catherine; Smiley, Tara M.; Terry, Rebecca; Davis, Edward B.; DeSantis, Larisa R.G.; Fox, David L.; Hopkins, Samantha S.B.; Jezkova, Tereza; Matocq, Marjorie D.; Matzke, Nick; McGuire, Jenny L.; Mulch, Andreas; et al.
Abstract : Topographically complex regions on land and in the oceans feature hotspots of biodiversity that reflect geological influences on ecological and evolutionary processes. Over geologic time, topographic diversity gradients wax and wane over millions of years, tracking tectonic or climatic history. Topographic diversity gradients from the present day and the past can result from the generation of species by vicariance or from the accumulation of species from dispersal into a region with strong environmental gradients. Biological and geological approaches must be integrated to test alternative models of diversification along topographic gradients. Reciprocal illumination among phylogenetic, phylogeographic, ecological, paleontological, tectonic, and climatic perspectives is an emerging frontier of biogeographic research. Trends: Topographically complex regions today feature high taxonomic and ecological diversity. Ancient topographic diversity gradients arose and declined over millions of years. Paleontological and modern data are crucial to understand topographic diversity gradients. Topographically complex regions have high conservation value.